THE ROLE OF DERMATOGLYPHICS IN MEDICINE: EXPLORING FINGERPRINTS FOR HEALTH INSIGHTS - Alisherov , T.A.; Shodmanov , B.B. (Educational Research in Universal Sciences, 2023)
Fingerprints, something so unique and personal, provide valuable information about a person’s health and genetic predisposition. The ability of dermatoglyphics to non-invasively diagnose certain genetic disorders is surprising, as it helps in early detection and intervention. The association between fingerprint patterns and certain health conditions, such as schizophrenia and multiple sclerosis, opens up opportunities for early screening and preventive measures. The study of pregnancy development through dermatoglyphics is an interesting field that provides information on developmental anomalies and pregnancy complications. The ability to identify prenatal exposure through fingerprinting may lead to targeted interventions and support for individuals exposed to substances during pregnancy. Incorporating dermatoglyphics into pharmacogenomic studies is a promising approach in personalized medicine, allowing for tailored treatments and minimizing adverse reactions. In addition to the points mentioned above, several research articles have explored the role of dermatoglyphics in various medical specialties. These studies have explored the use of fingerprints in areas such as forensic pathology, genetic counseling, prenatal screening, and even identifying individuals at risk for cardiovascular disease.